Acute Monocytic Leukaemia with Reactive Plasmacytosis - Dodhy, Mobina Ahsan; Habib, Maryam; Shaheen, Masooma; Abbasi, Masood (International Journal of Pathology, 2018)
An increased plasma cell count in bone marrow of patients of Acute Myeloid Leukaemia occurs in a subgroup ofpatients. There are very few case reports which document an increase in number of plasma cells at time of initialdiagnosis of Acute Myeloid Leukaemia. Here we present a case of 45- year old- male diagnosed as Acute MonocyticLeukaemia with Reactive Plasmacytosis, which posed much difficulty in diagnosis. The production of paracrineinterleukin- 6 by leukaemic blast cells is thought to cause this reactive increase in plasma cells.